Empowering Non-English Teachers Implementing English for Fun in Pantai Tinjau Village - Amelia Faddya Wildhani; Diah Safithri Armin; Annisa Nur Azizah; Tiara Fadiyah Rambe; Raihani; Melani; Ahmad Ridho Khuailid; Muhammad Akbar Rizky; Asti Ananta; Veriyansah (Association of Islamic Education Managers (Permapendis) Indonesia, North Sumatra Province, 2025)
This study aims to introduce English and empower non-English teachers at SD Negeri Pantai Tinjau, a rural school without formal English lessons. Using a descriptive qualitative approach, the program was implemented over three days with participatory and applicative methods. Activities included basic English introduction for grades 1–3 through nursery rhymes, a creative workshop for grades 4–6 to produce Classroom Expression Posters, and teacher training on using Vocabulary Wall and Classroom Expression Posters. The findings showed that students were enthusiastic and more willing to use simple English expressions, while teachers reported increased confidence in integrating English vocabulary into their lessons. The results indicate that simple, low-cost, and participatory media can effectively foster English exposure in rural schools and support teacher readiness, making it a viable model for replication in similar contexts.